1883 Mich. Pub. Acts 6 - (:unkn) unknown (My University, 1883)
No. 10, § 4: No person or persons shall at any time kill or attempt to kill, any wild duck or other wild fowl with or by means of a swivel or punt gun, or by means or use of any battery, sunken boat, or other device similar to a battery, or rob or destroy the nests of any wild duck or wild goose or brant, or in any manner kill or molest the same, at night or at any time, on their nesting places.
Keywords: HUNTING REGULATION